Does widowhood affect social capital in old age: the case of India - Choudhary, Akanksha; Singh, Ashish; Hifz Ur Rahman, Mohammad (Frontiers in Sociology, 2025)
PurposeIn India, widowhood, besides, being a personal status, presents itself as a social institution. Widows in India have long been deprived of normal living conditions and their hardships have been generally inconspicuous to policymakers as well as researchers. Therefore, this study is an attempt to understand the social dynamics of widowhood in India mainly through empirical means. It aims to examine the social capital of old widows through the lens of sociability, safety, and trust and solidarity.MethodsOrdered logistic regressions and Item Response Theory Partial Credit models with data drawn from the SAGE Study on Global Aging and Adult Health which was conducted across six populous states of India have been used for analysis.FindingsResults show that old widows experience significantly lesser sociability, trust and solidarity as compared to their married counterparts. Also, older widows from high income group are less vulnerable and have higher social capital compared to that of older widows from poorer income groups.DiscussionPolicy implications drawn based on the findings can play a vital role in uplifting the life of old widows in India significantly. This study is perhaps the first study to capture how widowhood affects the social capital in old age in India. Besides, based on the findings, we also suggest some policy initiatives to address the concern of low social capital among old widows in India.